The Effect of Cooperative Teaching with the Type of Numbered Headers on the Results of Teaching Arabic Writing - Rini Angreni Hasibuan; FNU Yunaldi (Indonesian Journal of Arabic Studies, 2022)
The results of the Arabic writing teaching in the Class VIII MTS Robi’ul Islam Pasar Latong, Lubuk Barumun Dtricist, Padang, Indonesia were not good because the teacher did not use the diverse education model. One of the education model is cooperative education in the Numbered Head Together type. This education can build actual education and promote cooperation between students in the discussion so that it can be influenced by the results of teaching Arabic writing The questions of this research are how to apply Numbered Head Together cooperative education? Has Numbered Head Together -type cooperative education affected the results of arabic writing education for VIII students at The MTS Robi’ul Islam Pasar Latong? The objectives of this research are to demonstrate the application of Numbered Head Together cooperative education and to see the impact of Numbered Head Together cooperative education on the results of arabic writing education for VIII students at The MTS Robi’ul Islam Pasar Latong.  The type of research is quantitative research in an experimental manner. The search population was all eighth class students، consisting of five classes with a total of 156 students. The number of students taken from class 8-A was 30 and the 8-B class was 31. Data collection is observed and tested. The data is processed and the data analyzed using the t. test formula after it has been studied by applying the remote test for experimental separation 83.70 and the control separation 78.65. The thitung> ttabel means 2,214 > 2,000  means that Ha is acceptable or there are cooperative effects of Numbered Head Together on the results of Arabic language education in the eighth semester of The MTS Robi’ul Islam Pasar Latong. The conclusion of this research is that there are cooperative effects of Numbered Head Together on the results of arabic writing education for VIII students at The MTS Robi’ul Islam Pasar Latong.